2021
DOI: 10.3390/nu13041060
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Management of Type 2 Diabetes in the MENA Region: A Review of the Evidence

Abstract: The alarmingly rising trend of type 2 diabetes constitutes a major global public health challenge particularly in the Middle Eastern and North African (MENA) region where the prevalence is among the highest in the world with a projection to increase by 96% by 2045. The economic boom in the MENA region over the past decades has brought exceptionally rapid shifts in eating habits characterized by divergence from the traditional Mediterranean diet towards a more westernized unhealthy dietary pattern, thought to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 205 publications
(255 reference statements)
0
13
0
1
Order By: Relevance
“…In this context, it is important to emphasize that, in order to be most effective, nutritional guidelines need to be developed according to several specific factors, such as local cultural, ethnic and traditional features, and geographic and socioeconomic components, as well as to the availability of specific local food products [ 9 ]. Among these features, the geographical location (i.e., a specific country, different areas in a country, such as seaside or mountainside or plains far from both, and specific latitude and climate, including climate changes, as well as the related social features) appears to be a crucial factor that may affect to a large extent the actual applicability of the Mediterranean diet or some of its principles as well as the actual adherence to it [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. An additional dynamic component affecting personal nutritional choices, also regarding adherence to the Mediterranean diet and its principles, is the individual life-long trajectory of food preference and nutrition habits and awareness, including feeding behavior aspects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is important to emphasize that, in order to be most effective, nutritional guidelines need to be developed according to several specific factors, such as local cultural, ethnic and traditional features, and geographic and socioeconomic components, as well as to the availability of specific local food products [ 9 ]. Among these features, the geographical location (i.e., a specific country, different areas in a country, such as seaside or mountainside or plains far from both, and specific latitude and climate, including climate changes, as well as the related social features) appears to be a crucial factor that may affect to a large extent the actual applicability of the Mediterranean diet or some of its principles as well as the actual adherence to it [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. An additional dynamic component affecting personal nutritional choices, also regarding adherence to the Mediterranean diet and its principles, is the individual life-long trajectory of food preference and nutrition habits and awareness, including feeding behavior aspects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, this aspect has been associated with local traditions and ethnic features and therefore remained rather stable over time within a specific population. However, over the last decades, due to the exponential diffusion of multiple communication media, the modifications of such traditional nutrition habits have been more frequent, leading to either a nutritional transition to unhealthy habits, especially in younger subjects [ 17 , 20 , 21 , 22 ] and in selected areas such as the Middle Eastern and North African (MENA) region [ 12 ], or a greater awareness of the health advantages of a good adherence to the Mediterranean diet, especially in middle/older age subjects, with improved nutrition patterns during their lifetime [ 23 ]. Thus, the epidemiological and experimental observations reporting adherence to the Mediterranean diet and its impact on health issues should also take into consideration another component: the time-related longitudinal changes within a specific population.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes among individuals aged 25-65 was 8.4% in 2004 and increased to 13.2% in 2016, which was higher than the worldwide average projected by International Diabetes Federation for 2017(8.4%) [ 21 ]. Similar to other countries located in the MENA region, Iran has witness an increasing trend in recent years, contributed by different factors including genetics, obesity, physical inactivity, urbanization, and poor nutritional habits [ 22 , 23 ]. In line with the present study, the prevalence of diabetes in most similar national studies was reported to be increasing, ranging from 7.4 to 24.5% [ 24 – 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well as, rising death rates due to poorly controlled Diabetes which is estimated to be responsible for 11.3% of fatalities worldwide. 2 …”
Section: Introductionmentioning
confidence: 99%